A clean global production network model considering hybrid facilities. (25th January 2021) - Mishra, Shraddha; Singh, Surya Prakash
Abstract: The paper presents a cleaner production and distribution model for global facility network that offers reverse logistics services under the warranty period. Hybrid manufacturing and storage facilities with flexible capacity are considered to save the extra setup and maintenance cost linked with establishing new reverse logistics facilities. The carbon emissions are accounted for the various activities related to product manufacturing and return. The carbon cap and trade policy is considered for regulating emissions. The dynamic mixed-integer non-linear programming (MINLP) model discussed in the paper optimizes the total cost of the network including costs associated with reverse logistics. The model is analysed on two hypothetical data sets. The results for the smaller data set reveal that the inventory holding is a better alternative to capacity expansion to deal with fluctuations in market demand. However, for the bigger data set, capacity expansion is recommended to satisfy the increased demand instead of relying completely on inventory management. The results are further analysed for varying carbon price and it is observed that increase in carbon price initially causes an increase in the carbon emissions but later it starts decreasing. This indicates that the increase in carbon price does not provide quick results and is more effective in controlling the emissions in the longer run. Furthermore, the proposed model investigates how different trade policies viz. free trade agreement (FTA), FTA with cap, and an increase in tariff barriers influence the total carbon emissions and the total cost. The results indicate that the total cost and the total emissions are relatively less under FTA with cap, however, there is a slight increase in the emissions of one country.